2023
DOI: 10.1186/s13098-023-01010-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on type 2 diabetes biomarkers: an umbrella of interventional meta-analyses

Abstract: Background Vitamin D supplementation exerts several supporting effects on improving glycemic status, however, results are inconclusive. Thus, in the present study, we aimed to conduct an umbrella of meta-analysis regarding the impact of vitamin D on type 2 diabetes (T2DM) biomarkers. Methods The Scopus, PubMed, Web of Science, Embase, and Google Scholar online databases were searched up to March 2022. All meta-analyses evaluating the impact of vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 89 publications
1
10
0
1
Order By: Relevance
“…The intervention led to significant improvements in energy and macronutrient intake, body weight, insulin sensitivity, and blood lipid profiles. These findings resonate with earlier studies demonstrating the benefits of vitamin D3 and probiotics on metabolic health [1][2][3][4][5][6]. The observed synergistic effect highlights the potential of combining these bioactive compounds in a dietary matrix.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The intervention led to significant improvements in energy and macronutrient intake, body weight, insulin sensitivity, and blood lipid profiles. These findings resonate with earlier studies demonstrating the benefits of vitamin D3 and probiotics on metabolic health [1][2][3][4][5][6]. The observed synergistic effect highlights the potential of combining these bioactive compounds in a dietary matrix.…”
Section: Discussionsupporting
confidence: 89%
“…Similar outcomes were observed in patients with type 2 diabetes, in which a 12-week regimen yielded substantial metabolic improvements [35]. A recent umbrella of 37 interventional meta-analyses reported that vitamin D supplementation significantly decreased fasting blood glucose, HbA1c, insulin, and HOMA, mainly in individuals with type 2 diabetes and women with gestational diabetes, as well as resulted in vitamin D dosages lower than or equal to 4000 IU [1]. The antidiabetic effects of probiotics include reducing proinflammatory cytokines via the NF-κB pathway, reducing intestinal permeability, and lowering oxidative stress [30].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Hence, such AEDT-induced adaptations may be associated with the potential activation of some key molecular mechanisms responsible for regulating glucose metabolism linked to visceral and ectopic fat [ 69 , 70 ]. In summary, non-pharmacological anti-obesity agents, such as regular physical exercise, patient-centred diet and proper supplementation can be used in conjunction with prescribed medications to noticeably improve T2DM biomarkers [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D prevents epigenetic alterations associated with IR, and vitamin D de ciency is one of the factors accelerating IR formation [8]. Additionally, studies have con rmed that vitamin D supplementation reduce the level of metabolic parameters such as TC, LDL-C, TG, glycated hemoglobin (HbA1c), as well as decreases HOMA-IR in patients with T2DM [9][10].…”
Section: Introductionmentioning
confidence: 99%